Reply to Zvuloni, A.; Shaked, Y. Comment on “Shashar et al. Artificial Reef Deployment Reduces Diving Pressure from Natural Reefs—The Case of Introductory Dives in Eilat, Red Sea. Oceans 2024, 5, 71–80” - Nadav Shashar; Re’em Neri; Asa Oren; Jenny Tynyakov (Oceans)
In a recent study [...]